Annual compost amendments can replace synthetic fertilizer, improve soil moisture, and ensure tree performance during peach orchard establishment in a humid subtropical climate - Lawrence, Brian T.; Melgar, Juan Carlos (Frontiers in Plant Science, 2023)
The application of organic matter (OM) to peach orchards is currently uncommon in commercial operations but could potentially replace synthetic fertilizers and improve long-term orchard sustainability. The purpose of the following study was to monitor how annual applications of compost to replace synthetic fertilizer would change soil quality, peach tree nutrient and water status, and tree performance during the first four years of orchard establishment within a subtropical climate. Food waste compost was incorporated before planting and added annually over four years with the following treatments: 1) 1x rate, applied as dry weight at 22,417 kg ha-1 (10 tons acre-1) incorporated during the first year and 11,208 kg ha-1 (5 tons acre-1) applied topically each year after; 2) 2x rate, applied as dry weight at 44,834 kg ha-1 (20 tons acre-1) incorporated during the first year and 22,417 kg ha-1 (10 tons acre-1) applied topically each year after; and 3) control, with no compost added. Treatments were applied to a virgin orchard location, where peach trees had never previously been grown, and to a replant location, where peach trees had been grown previously for more than 20 years. Synthetic fertilizer was reduced in the 1x and 2x rates by 80 and 100% during the spring and all treatments received the summer application according to standard practice. Soil OM, phosphorus and sodium all increased with the addition of 2x compost in the replant location at 15 cm depth, but not within the virgin location compared to the control treatment. The 2x rate of compost improved soil moisture during the growing season, but tree water status was similar between treatments. Tree growth was similar between treatments in the replant location, but the 2x treatment had larger trees compared to the control by the third year. Foliar nutrients were similar between treatments over the four years, while 2x compost rate increased fruit yield in the virgin location compared to the control the second year of harvest. The 2x food waste compost rate could be considered as a replacement for synthetic fertilizers and to potentially increase tree growth during orchard establishment.